Fenomenologiczna "Zasada wszelkich zasad" jako odejście od Kantowskiej koncepcji czysto dyskursywnego charakteru intelektu - Jeziorski, Marcin (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2010)
Within the content of the following paper I aim to reveal some epistemological benefits, related to Husserl's concept of an eidetic intuition. In order to do so, I refer to Kant's radical division of the subject's cognitive activity into two main epistemic faculties, namely intuition, which – according to Kant's statements – may be just empirical, and being strictly and only discursive intellect. Having presented it I further proceed to describe certain difficulties, being the result of the rejection of possibility of an intuitive use of intellect, such as the objective validity of cognizing an apriorical forms, or the process of creating an empirical notions. Finally I refer to Husserl's acceptation of an eidetic intuition, being – according to my opinion – the only way of solving all the problems presented above.